DYNAMIC AND STATIC NETWORKING: MAIN IDEAS AND NATURE, SPECIFICS IN A COUNTRY WITH EMERGING MARKET - Valdaytsev, Sergey; Gordeev, Igor; Samilov, Ivan (Ekonomika, 2013)
Abstract. The objective of the article is to systematize the dynamic and especially static entrepreneurial networks as they look, appear, and act in a country with so-called emerging markets. This is accomplished on the example of Russia. Special attention is paid to relevant business goals and patterns to typical members of such networks, to why, when and how one passes from outsourcing in dynamic networks to static networking.The article contains a field research based on (1) access to public databases like Spark-Interfax in Russia, with updated information on registered firms (their founders, affiliated companies, businesses) and (2) interviews with businessmen who agreed to comment on the problems under discussion.As regards the results of the research, two points seem to be especially important. First, when, according to legislation, information on registered firms and their statistical reports is public, it is not too problematic to find out and monitor the activities of practically all types of business static networks in all industries. Second, when the business environment becomes more competitive, dynamic networks tend to be transformed into static ones not only due to considerable contract risks, but also because one needs to select from wider samples of possible suppliers the most competitive and those who are ready to invest into the technological innovations.The general conclusion is that in countries with a dynamic economic growth and increasing competitiveness of the business environment, like in Russia, this advantage of static networking might prevail, especially if static networks appear as a result of selecting business partners from the firm’s experience in outsourcing.Key words: static and dynamic networks, outsourcing, information networking, affiliated companiesp>